Does Entrepreneurial Activity Affect Entrepreneurial Success in Developing Countries? Data Evidence from Cameroon - Seugue Nietcho, John William; David Léo, Leumani Pameni; Dongmo Feulefack, Pierre Armandv (Acta Universitatis Danubius. Œconomica, 2023)
This article aims to analyze the effect of start-up activities on entrepreneurship in developing countries, using the example of Cameroon. For this fact, we used logistic regression, on a sample of 614 entrepreneurs extracted from the CRDI database collected in 2014. The results show that contrary to the existing literature, in Cameroon most of these activities negatively influence the start-up of entrepreneurship, with the presence of individual and spatial heterogeneity. More precisely, almost at all levels of distribution, the results show a very significant and negative correlation of formalization on the start of entrepreneurship. In view of these results, we recommend to decision-makers and organizations responsible for promoting entrepreneurship to thoroughly review the procedure for formalizing businesses in Cameroon, to review the content of training and education in order to convey the modules related to business start-ups.